Potential Thermal Enhancement of Lightweight Building Walls Derived From Using Phase Change Materials (PCMs) - Sun, Xiaoqin; Medina, Mario A.; Zhang, Yuan (Frontiers in Energy Research, 2019)
This paper presents results of the potential thermal enhancement in building walls derived from using phase change materials (PCMs). Typical North American construction, namely, frame walls outfitted with hydrated-salt-based PCM were evaluated in well-controlled test houses under full weather conditions. It was found that PCMs produced reductions in energy gains during summer. The reductions were assessed via total heat transfer and peak heat transfer. For a 10 percentage by weight (wt%) PCM concentration, the largest peak flux reduction of 31.25% was observed when the PCM was integrated within a north-facing wall. For a 20 wt% PCM concentration, the largest peak flux reduction was 25.54% when the PCM pipes was installed on an east-facing wall. Doubling the amount of PCM did not produce improvement on heat flux reduction except for the east-facing wall. The indoor wall surface temperature and temperature amplitude was reduced by 1.5 oC and 1.4 oC, respectively. The maximum time lag for peak heat flux was observed on the north-facing wall, which was 1.5 hours for a 10 wt% PCM concentration and 2.25 hours for a 20 wt% PCM concentration, respectively. To achieve the maximum energy savings, it is recommended that the PCMs be installed within west-facing walls.